Encouraging Creativity: Reading and Writing Short Stories - Satri Efendi, Ali; yakub, Sudirman (ASIAN PUBLISHER, 2022)
This article focuses on the use of short stories in the process of learning English for grade 6 students at Al Fath School Indonesia, especially in imrpoving reading and writing skill. Every year, Al Fath students take special training in writing short stories. They study plot structure diagrams and compare them with the short stories they read, then they write their own short stories. The results of the short stories that the children wrote were then analyzed and collected into an anthology book with ISBN. This article is expected to provide an overview and example for schools to encourage students' creativity in reading and writing activities